Construction and Multiple Exterior Surface Functionalization of Giant Molecular Cages. Issue 35 (30th October 2014) - Naseer, Muhammad Moazzam; Wang, De‐Xian; Zhao, Liang; Wang, Mei‐Xiang
Abstract: By a one‐pot reaction strategy and a stepwise fragment‐coupling approach, three types of giant cage molecules with a triangular prism shape and an approximate cavity volume of 930 Å 3 were synthesized. Through efficient aromatic nucleophilic substitution reactions of chlorotriazine with functionalized amines or aliphatic substitution reactions of the linking imino moieties with allyl bromide, the giant cages were successfully functionalized on the surface with multiple hydroxy, 2‐pyridyl, or allyl groups. As evidenced by variable‐temperature 1 H NMR spectroscopy, the D 3 h ‐ and C 3 v ‐symmetric cage molecules underwent very slow conformational changes or deformation in solution because of their giant size and their flexible building units. Their giant cavities, different electronic interiors, and facile multiple exterior surface functionalization could render the molecular cages powerful three‐dimensional macrocyclic hosts that might find wide applications in supramolecular science. Abstract : Giant cage molecules with D 3 h ‐ and C 3 v ‐symmetric triangular prism shapes are synthesized by a one‐pot reaction method through a stepwise fragment‐coupling approach. Multiple functionalizations on the cage surface with hydroxy, 2‐pyridyl, and allyl groups have been implemented by aromatic nucleophilic substitution reactions of chlorotriazine with amines or aliphatic substitution reactions.